The Role of Bilirubin in Diabetes, Metabolic Syndrome, and Cardiovascular Diseases - Vitek, Libor (Frontiers in Pharmacology, 2012)
Bilirubin belongs to a phylogenetically old superfamily of tetrapyrrolic compounds, which have multiple biological functions. Although for decades they were believed to be only a waste product of the heme catabolic pathway at best, and a potentially toxic compound at worst; recent data has convincingly demonstrated that mildly elevated serum bilirubin levels are strongly associated with a lower prevalence of oxidative stress-mediated diseases. Indeed, serum bilirubin has been consistently shown to be negatively correlated to cardiovascular diseases (CVD), as well as to CVD-related diseases and risk factors such as arterial hypertension, diabetes mellitus, metabolic syndrome, and obesity. In addition, the clinical data are strongly supported by evidence arising from both in vitro and in vivo experimental studies. This data not only shows the protective effects of bilirubin per se; but addionally, of other products of the heme catabolic pathway such as biliverdin and carbon monoxide, as well as its key enzymes (heme oxygenase and biliverdin reductase); thus, further underlining the biological impacts of this pathway. In this review, detailed information on the experimental and clinical evidence between the heme catabolic pathway and CVD, and those related diseases such as diabetes, metabolic syndrome, and obesity is provided. All of these pathological conditions represent an important threat to human civilization, being the major killers in developed countries, with a steadily increasing prevalence. Thus, it is extremely important to search for novel markers of these diseases, as well as for novel therapeutic modalities to reverse this unfavorable situation. The heme catabolic pathway seems to fulfill the criteria for both diagnostic purposes as well as for potential therapeutical interventions.